Genetic diversity of next generation antimalarial targets: A baseline for drug resistance surveillance programmes. Issue 2 (August 2017) - Gomes, Ana Rita; Ravenhall, Matt; Benavente, Ernest Diez; Talman, Arthur; Sutherland, Colin; Roper, Cally; Clark, Taane G.; Campino, Susana
Abstract: Drug resistance is a recurrent problem in the fight against malaria. Genetic and epidemiological surveillance of antimalarial resistant parasite alleles is crucial to guide drug therapies and clinical management. New antimalarial compounds are currently at various stages of clinical trials and regulatory evaluation. Using ∼2000 Plasmodium falciparum genome sequences, we investigated the genetic diversity of eleven gene-targets of promising antimalarial compounds and assessed their potential efficiency across malaria endemic regions. We determined if the loci are under selection prior to the introduction of new drugs and established a baseline of genetic variance, including potential resistant alleles, for future surveillance programmes. Graphical abstract: Highlights: Genetic diversity of 11gene-targets of new antimalarial compounds was investigated. Genetic data was analysed for 18 malaria endemic countries. No signals of selective pressure was observed. A mutation linked to resistance to a new antimalarial was found in African parasites. Amino-acid changes close to reported antimalarial resistant mutations were detected.